Strategi Bagian UMPEG dalam Peningkatan Disiplin Kerja Pegawai Dinas Perumahan Rakyat dan Kawasan Permukiman Provinsi Banten - Naufal Laksana Riki; Delly Maulana (Universitas Medan Area, 2026)
This study aims to analyze the strategies of the General and Personnel Section (UMPEG) in enhancing employee work discipline at the Housing and Settlement Area Office of Banten Province. A qualitative descriptive approach was employed to examine the interaction of internal and external factors affecting discipline, leadership strategies, control mechanisms, and organizational culture reinforcement. The findings indicate that employee discipline is influenced by internal factors, such as attitude, personality, and individual readiness, as well as external factors, including environmental influences and weather conditions. UMPEG’s disciplinary strategies are reflected through communicative and consistent leadership, well-managed regulations, and the creation of a conducive work environment. Implementation is carried out through attendance monitoring, direct supervision, periodic evaluations, and recognition of highly disciplined employees. These results underscore that employee discipline is a product of the synergy between leadership, organizational management, and the internalization of disciplinary values, contributing to organizational productivity and sustainable public service performance.